2010
DOI: 10.1007/s10511-010-9118-9
|View full text |Cite
|
Sign up to set email alerts
|

Conformal analogs of the Jordan-Brans-Dicke theory. I.

Abstract: Recent cosmological observations of large-scale structures (red shift of type Ia supernovae) confirm that the universe is currently expanding at an accelerating rate and its dominant component is dark energy. This has stimulated the development of the theory of gravity and led to many alternative variants, including tensor-scalar ones. This paper deals with the role of conformal transformations in the Jordan-BransDicke theory. Variants of intrinsic, conformally coupled, and Einstein representations are examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Here we consider the de Sitter cosmological model in the proper presentation of the JBD theory with P = 0, ε = 0, ϕ(y) = αH 2 . The equations for the standard cosmological model, corresponding to the modified action of the JBD theory [4]…”
Section: Uniformly Accelerated Expansion Of the Universementioning
confidence: 99%
See 1 more Smart Citation
“…Here we consider the de Sitter cosmological model in the proper presentation of the JBD theory with P = 0, ε = 0, ϕ(y) = αH 2 . The equations for the standard cosmological model, corresponding to the modified action of the JBD theory [4]…”
Section: Uniformly Accelerated Expansion Of the Universementioning
confidence: 99%
“…By taking into account known considerations [4] on the existence of the relationship between Λ and the Hubble parameter H, in the first section of the paper we assume that ϕ(y) = αH 2 . This assumption can also be argued on the base of the time-dependence of H given in [5], where it has been shown that in the limit t → ∞ one has H 2 = Λ/3.…”
Section: Introductionmentioning
confidence: 99%